2018
DOI: 10.5430/wje.v8n5p130
|View full text |Cite
|
Sign up to set email alerts
|

Digital Educational Game Usage Scale: Adapting to Turkish, Validity and Reliability Study

Abstract: The purpose of this study is to adapt Digital Educational Games Usage Scale (DEGUS) that was developed byBonanno & Kommers (2008) to Turkish with the companion of a group of university students studying in departmentof English Teaching. In order for scale items to be the same in terms of language, firstly the translations of the itemswere carried out both from English to Turkish and Turkish to English, afterwards examining the forms gathered fromthe students, significant and positive correlations were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this study, it was aimed to evaluate the use of educational digital games by teacher candidates. In this context, to serve the purpose; It was used as a data collection tool from the scale adapted to Turkish by Sarıgöz, Bolat, Alkan developed [13] by Bonanno and Kommers. The scale consists of 21 items.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, it was aimed to evaluate the use of educational digital games by teacher candidates. In this context, to serve the purpose; It was used as a data collection tool from the scale adapted to Turkish by Sarıgöz, Bolat, Alkan developed [13] by Bonanno and Kommers. The scale consists of 21 items.…”
Section: Methodsmentioning
confidence: 99%
“…Digital Educational Game Perception Scale developed by Sarıgoz et al (2018) was used in this study. "Exploratory and confirmatory factor analyses revealed that the scale had four dimensions.…”
Section: 1data Collection Toolmentioning
confidence: 99%
“…In item total correlation calculation of the scale it was observed that all the items were above .40, item factor loads varied between .51 and .68, Cronbach Alpha internal consistency coefficient was .78 and test retest correlation was .88. Significant relations were in the calculations regarding the correlation analyses of the scale" (Sarıgoz et al, 2018).…”
Section: 1data Collection Toolmentioning
confidence: 99%
“…The affective components are the feelings of fear, hesitation and irritability before and during the play. Students' willingness or unwillingness to play games are also behavioral components (Sarıgöz, Bolat & Alkan, 2018). Making positive contributions to students' perceived control and benefit, affective and behavioral components with the help of digital games can help shape students' emotions and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Making positive contributions to students' perceived control and benefit, affective and behavioral components with the help of digital games can help shape students' emotions and behaviors. In fact, it is aimed to provide emotional and behavioral participation in the games and to satisfy the students by entertaining them (Sarıgöz, Bolat & Alkan, 2018). The positive development of students' emotions and behaviors with digital games makes significant contributions to many different variables for lessons.…”
Section: Introductionmentioning
confidence: 99%